2016
DOI: 10.1002/cjce.22382
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on hydrodynamics of vertically confined free film

Abstract: For intensification of the film transfer process, flow behaviours of a novel type of liquid film, “confined free film” (a coexistence of both wall‐bounded and unbounded films), on a vertically‐aligned plate with an open window were investigated using the CFD modelling approach. It was found from the simulations that the liquid flow profiles of confined free film in the region of the open window vary with flow time. The average film thickness of the confined free film in the open window region is approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…According to Lin's, at a slightly larger Weber number than the transition Weber numbers, the surface tension suppresses the varicose waves but promotes the sinuous waves, which are the vehicle of absolute instability. As mentioned by Hu, the region of the lower‐wall plate promotes both varicose and sinuous wavy behavior of the confined free film, while the open‐window region assists the exciting of the film wave motion in the lower‐wall region. This can be explained by a mutual promotion and restraint between wave profile in the window and distribution of liquid flow on two sides of lower wall.…”
Section: Numerical Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…According to Lin's, at a slightly larger Weber number than the transition Weber numbers, the surface tension suppresses the varicose waves but promotes the sinuous waves, which are the vehicle of absolute instability. As mentioned by Hu, the region of the lower‐wall plate promotes both varicose and sinuous wavy behavior of the confined free film, while the open‐window region assists the exciting of the film wave motion in the lower‐wall region. This can be explained by a mutual promotion and restraint between wave profile in the window and distribution of liquid flow on two sides of lower wall.…”
Section: Numerical Resultsmentioning
confidence: 94%
“…Later, Hu et al analyzed the primary characteristics of the “confined free film” with two‐dimensional (2D) numerical simulations. It was revealed that there exist two types of vortices inside the film, inner vortices and interfacial vortices, which is well related to local mass transfer rate.…”
Section: Introductionmentioning
confidence: 99%
“…Eng . mention XRD to characterize polymers, composite materials, catalysts, membranes, minerals, and medicinal drugs, which makes it one of the most used spectrometries.…”
Section: Introductionmentioning
confidence: 99%
“…4 Numerous effort has been done to predicate the mass transfer process and obtaining knowledge of the absorption process for an FFR. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The mass transfer rates are investigated for the wavy and smooth falling film. The investigation has shown that the mass transfer rate was bigger for the wavy film and mass transfer characteristics varied substantially with the wave regime.…”
Section: Introduction *mentioning
confidence: 99%
“…[6][7][8][9] The film hydrodynamics, such as the velocity distributions and the vorticity variations at different positions of the wavy falling films, have been enhanced the mass transfer process. 10 The analytical and numerical model has been applied to model FFR [6][7][8][9][10][11][12] and FFR could be simulated by means of COMSOL Multiphysics. 13,14 Generally, the two-film theory is used to describe gas absorption.…”
Section: Introduction *mentioning
confidence: 99%